A Religious People: Political Philosophy, Civil Religion and the American Polity - William F Baumgarth (Journal of Dharma, 1982)
Even as vehement a critic of religion as Karl Marx had to concede that the exorcism of theological belief from the basis of political life, its reduction to mere private belief. had not led. in the instance of the American republic. to a withering away of the opiate of the masses. This, for Marx. bespoke a defect in republican government itself.’ We will not be crueL enough to suggest that. were he present now. his anti- theological ire might lead him to an equally vehement criticism of regimes that produce the like of Solzhenitsen.